2018
DOI: 10.1021/acs.langmuir.8b01471
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Titanium Dioxide Gel with Encapsulated Bacteriorhodopsin for Hydrogen Production

Abstract: We study bacteriorhodopsin (BR) in its native purple membrane encapsulated within amorphous titanium dioxide, or titania, gels and in the presence of titania sol particles to explore this system for hydrogen production. Förster resonance energy transfer between BR and titanium dioxide sol particles was used to conclude that there is nanometer-scale proximity of bacteriorhodopsin to the titanium dioxide. The detection of BR-titania sol aggregates by fluorescence anisotropy and particle sizing indicated the affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These structures have been utilized in the development of solar cells, increasing their efficiency and representing a potential alternative for the development of energy conversion systems. bRs have also been used when functionalized with TiO 2 gel in the presence of platinum nanoparticles for hydrogen production [ 213 ]. Under these conditions, it was observed that bRs did not denature even in the presence of ethanol or methanol, and the hydrogen production from these hybrid structures was 52% higher than that observed in the absence of bR.…”
Section: Biomimetic Approachesmentioning
confidence: 99%
“…These structures have been utilized in the development of solar cells, increasing their efficiency and representing a potential alternative for the development of energy conversion systems. bRs have also been used when functionalized with TiO 2 gel in the presence of platinum nanoparticles for hydrogen production [ 213 ]. Under these conditions, it was observed that bRs did not denature even in the presence of ethanol or methanol, and the hydrogen production from these hybrid structures was 52% higher than that observed in the absence of bR.…”
Section: Biomimetic Approachesmentioning
confidence: 99%
“…Both the sensitizer and photon pumping activity of bR has been leveraged in heterogeneous and homogeneous catalytic systems for light driven hydrogen production. Crystalline [143] and amorphous [144] TiO2 suspensions combined with bR, a sacrificial reductant (e.g., methanol), and Pt catalyst can generate H2 under illumination with visible light. In a related study, Allam et al observed a more negative onset potential and increased photocurrent densities with bR coated TiO2 nanotube based photoanodes compared to the same electrodes without bR under photochemical conditions for solar water splitting [145].…”
Section: Bacteriorhodopsin As a Catalyst To Improve Device Performancesmentioning
confidence: 99%
“…Both protein–pigment complexes have shown remarkable thermal stability and their structural, biochemical, and photophysical properties have been extensively studied [ 15 , 16 ]. Similarly, both PSI and bR have also been widely used in a variety of biotechnological applications, most notably in BSSCs [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%